Functional Training Focused on Motor Development Enhances Gross Motor, Physical Fitness, and Sensory Integration in 5–6-Year-Old Healthy Chinese Children - Fu, Tao; Zhang, Diruo; Wang, Wei; Geng, Hui; Lv, Yao; Shen, Ruiheng; Bu, Te (Frontiers in Pediatrics, 2022)
Objective: Physical inactivity and sensory integration dysfunction are public health concerns among Chinese preschool children. The purpose of this study was to determine the efficacy of a novel functional training program focused on motor development for healthy children aged 5 to 6 years. Methods: A total of 101 healthy children aged 5 to 6 years in Tianjin were randomly assigned to the experimental group (N = 51), which received 12-week functional training featuring essential motor skills, whilst the control group (N = 50) continued with their kindergarten-based physical education curriculum. Test of Gross Motor Development-2, national physical fitness measurement, and sensory integration were evaluated before and after the intervention. Children's height, body weight, and the corresponding pre-intervention test scores were utilized as covariates to compare the post-intervention outcomes between the groups. Results: After the intervention, the experimental group scored considerably higher (P < 0.01) on the locomotor composite score, object control composite score, and overall gross motor score than the control group; the experimental group scored higher (P < 0.05) on the run, gallop, leap, stationary dribble, kick, striking a stationary ball, overhand throw, and underhand roll motor skill tests than the control group; the experimental group performed considerably better (P < 0.01) on the balance beam walking test and sit-and-reach test than the control group; and, the experimental group performed considerably better (P < 0.01) on the vestibular function, tactile defensiveness, and proprioception than the control group. Conclusion: A 12-week functional training focused on motor development effectively enhanced gross motor, physical fitness, and sensory integration in 5–6-year-old healthy Chinese children.